The Influence of Halal Seasoning Issues on Consumer Awareness and Purchase Interest: A Study of the Royco Brand in Cipedak and Cinere Districts - Alini Indriana Utari; Resman Muharul Tambunan; Veranus Sidharta; Anisti Anisti; Syatir Syatir (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Royco is one of the popular seasoning brands in Indonesia. However, increasing consumer awareness regarding halal issues has raised concerns about the product's halal status. Given that Royco seasoning is widely used in daily cooking, ensuring its halalness becomes critical. This study aims to examine the influence of halal issues on consumer awareness and purchase interest toward Royco products in the Cipedak and Cinere Districts. A quantitative explanatory research method was employed using an online survey distributed through Google Forms, and the data were analyzed with the SEM-PLS technique using SmartPLS 3.2.9 software. The findings show that the halal issue has a significant direct effect on purchase interest (22.3%) and an indirect effect through consumer awareness (17.3%). Furthermore, the halal issue strongly influences consumer awareness (50.2%), which subsequently contributes to an increase in purchase interest (34.6%). These results highlight that clarifying and disseminating information about the halal status of products not only directly boosts consumer purchase interest but also enhances consumer awareness, which in turn strengthens purchase interest. The study implies that companies must prioritize transparent halal certification communication to maintain and increase market trust and purchasing behavior.